Introduction of Paeonia tenuifolia L. in the dendrological park "Askania Nova" (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The process of Paeonia tenuifolia L. ontogenesis is studied when cultivating in the Dendropark “Askania Nova”, Southern Ukraine steppe zone. The phenorhythmics, peculiarities of individual development and reproduction, morphometric parameters of vegetative and generative organs are established. The last are characterized by a very low (length of a petal and fruit), low (height of a plant and peduncle, petal width, length and width of the seed), and average (leaf’s length and width, the width of a fruit) levels of variability that indicates substantial adaptation of the species in the new growth conditions. It has been determined that Paeonia tenuifolia is characterized by full realization of annual and life development cycles. Plants are well-developed, regularly bloom and fruit and form a viable self-seeding. There is a tendency to form introduction population of the species.
Keywords: Paeonia tenuifolia L., conservation ex situ, peculiarities of individual development, reproduction indices.